Chaotic signals in digital communications - Eisencraft, Marcio; Attux, Romis R.; Suyama, Ricardo (Boca Raton, [Florida] : CRC Press, 2013)
'This book provides the reader with a series of techniques that can be employed in the chaos-based communication systems proposed in the literature, in order to attain consistent performance in realistic environments. The ideas outlined in this book will help to form a bridge between theoretical works and practical implementations. Therefore, this book should be of interest to theoretical researchers, showing possible shortcomings of the proposed systems when subjected to non-ideal conditions, and to those interested in actually implementing such systems'--
Includes bibliographical references and index.
Keywords: Signal processing; Digital communications; Chaotic behavior in systems